RECOMMENDATIONS FOR STRUCTURAL MITIGATION MEASURES AGAINST TSUNAMI THREATS (CASE STUDY: PALU CITY - Jabbar, Andi Tenri Khalik (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The development of various countries in disaster awareness should serve as a reference for Indonesia, a region located at the convergence of four tectonic plates that is prone to tsunami disasters. While tsunamis cannot be prevented, they can be minimized through both structural and non-structural disaster mitigation measures. This literature review aims to examine case studies of regions that have successfully implemented structural mitigation measures and to propose several recommendations for structural mitigation based on spatial analysis and experimental testing of structural mitigation forms. From the compilation of literature studies, appropriate disaster mitigation forms can then be adopted for implementation in each region as a step to confront the threat of tsunami disasters. The case study in this research is Palu City, to implement the recommended structural mitigation measures that have been studied. The results of this research present five recommended forms of structural tsunami disaster mitigation that can be implemented in Palu City: construction of tsunami gates at river mouths, planting mangroves as green belts, construction of seawalls, breakwaters, and enforcement of appropriate coastal setback distances.